The Effect of Group Counseling with Problem Solving Techniques on Learning Time Management for Students - Irawan, Mirza; Miswanto, Miswanto; Violina, Erwita Ika; Brio, Bicer (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2024)
This study was conducted with the aim to determine the effect of problem solving techniques group guidance on time managamenet learning of eighth grade students Abu Daud in SMP Islam Terpadu Nurul Fadhilah. This research method is a quantitative method with the type of experimental research, the design used in the study is One-Group Pretest-Posttest Design. The research subjects were 10 people from Class VIII Abu Daud. The data were collected using the time management learning scale. Data analysis techniques using Wilcoxon Test with the help of SPSS for Windows version 27. The results obtained an average pre-test with a score of 159.7 and an average post-test with a score of 176.1. Based on the results of pre-test and post-test, the difference in scores was 194 with a percentage of 19.4% so that there was an increase in student learning time management. While the results of the hypothesis test Asymmp. Sig. (2-tailed) is 0.005<0.05 with the criteria if the value is asymptotic. Sig. (2-tailed) obtained less than 0.05 then there is a significant difference in the level of learning time management before and after following the guidance Group problem solving techniques. H0 rejected and H1 accepted, it can be concluded that the results showed that there is an influence of problem solving techniques group guidance on learning time management of eighth grade students Abu Daud SMP it Nurul Fadhilah T.A 2023/2024.